Gazeous diffusion characteristics in some sedentary soils of Peninsular Malaysia - Gulam Mohammed Hashim (Kuala Lumpur (Malaysia), 2016)
The, soils with higher aggregate stability exhibit lower gaseous diffusion within aggregates, and aggregate size modifies the influence of water content on gaseous diffusion. In general, gaseous diffusion increases with a decrease in water content, but in a soil consisting of large aggregates this relation is only true at values of aeration porosity 0.32. When subjected to disruptive forces, soils with relatively lower aggregate stability experience a reduction in gaseous diffusion